MASSIVE, OPEN, ONLINE: LEARNING PARALLEL OR TOGETHER? - Ivan Yu. Travkin (Высшее образование в России)
The author considers two major types of learning community design in MOOCs - massively cooperative (connectivists cMOOC) and massively parallel (xMOOC: Coursera, Udacity, Khan Academy, etc.). Being focused on massively cooperative type, the paper also shows that cMOOCs foster the development of personal learning and its tools. The author comes to a conclusion that while the development of xMOOCs means creation of the "broadcasting" infrastructure, cMOOCs are aimed towards a new culture of massively-cooperative distance learning.